Mekanisme Pembiayaan Tabungan Umum Syari’ah : (Studi Kasus BMT Maslahah Capem Gending Probolinggo) - Yeni Kartikawati (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
This general sharia savings product is a deposit which in principle is a pure savings from the party who keeps it or entrusts it to the party who receives the deposit for use or not in accordance with the contract used. Sharia general savings itself has a mechanism where the mechanism is an important thing for banking. Knowing the financing mechanism will attract people's interest in saving or making loans to the cooperative. If the BMT mechanism is well organized it will also increase public trust in carry out transactions in the cooperative. The interesting thing about why researchers want to examine the general sharia savings financing mechanism is because when conducting observations and interviews the researchers found a positive response from members who saved. The focus of this research is how the general sharia savings mechanism at BMT Maslahah Capem Gending is used so that members can understand the mechanism to determine member responses and member growth in saving. This research uses a descriptive-qualitative approach by conducting observations, interviews with the head of the BMT Maslahah Capem Gending branch and members, supported by several journals related to general sharia savings. The results of research at BMT Maslahah Capem Gending regarding the sharia general savings financing mechanism have been running well and efficiently so that the growth of savings members increases from year to year.